(3eMJhjGJ ShQ GdbQBf GdcQje (B/s - (3GdWhjd, CMeO Hf CMeO Hf eMeO YHO Gddgs ((3GdQjGV (B:s (3eOGQ GdhWf ddfTQ,s, 2013)
(3jJfGhd cJGH (B((3eMJhjGJ ShQ GdbQBf GdcQje(B) (3hGdPj bGe HJCdjag CMeO Hf CMeO Hf eMeO YHO Gddg GdWhjd, ehVhY (B((3GdbQBf GdcQje(B) (3GdcJGH jVe ebOeI dcd ShQI ef ShQ GdbQBf, hHjGf eYGfj GdBjGJ heG ajgG ef JTQjY hCMcGe hCSQGQ, hYHQ hgOGjGJ, heaQOGJ, eY HjGf GdeYfi GdELeGdj GdeOYe HGdBjGJ GdeeGKdI hGdeTGHgI, hCSHGH GdfRhd, hGdCMGOjK GdfHhjI, hCbhGd GdUMGHI hGdJGHYjf, hGdCMcGe GdabgjI, hQHW Pdc HGdCMOGK GdeYGUQI(B. (3ceG JfGhd aj cd ShQI YfGUQ GdShQI hCZQGVgG, hebGWYgG, hehVhYGJgG, hYOO BjGJgG, hcdeGJgG hMQhagG, hCSeGFgG(B. s
Keywords: (3JaSjQ GdbQBfs